Undergraduate Men’s Self-Reports of Sexual Assault and Perceptions of College Campus Acquaintance Rape - McDaniel, M. Colleen (Journal of interpersonal violence, 2021)
Acquaintance rape is distressingly common on college campuses. Differing models of the perpetration of sexual assault make diverging predictions regarding the degree to which individual differences may distinguish among such sexual offenders and nonoffenders. Much research investigating these issues has primarily sampled students from large, commuter colleges. Such data may not generalize to students in other university settings (e.g., private schools, students in university housing). The present study sought to examine the rate of self-reported sexual assault among college men at a private school at which most students live in university housing. Furthermore, we examined whether individual difference characteristics—namely, endorsement of masculine gender norms and endorsement of modern myths about sexual assault—predicted participants’ perceptions of acquaintance rape. A total of 219 college men completed a survey consisting of the Male Role Norm Inventory (MRNI), followed by the Acceptance of Modern Myths About Sexual Aggression (AMMSA) and the Sexual Experiences Survey (SES). They then read a hypothetical acquaintance rape scenario and provided several ratings regarding their attributions of blame. Approximately, 4.6% of men self-reported having committed sexual assault. A Bayesian analysis indicated that self-reported offenders did not score differently on MRNI and AMMSA than self-reported nonoffenders, nor did they view the hypothetical scenario differently. Overall, men who endorsed male role norms tended to accept modern myths about rape and tended to attribute more blame to the victim and less blame to the perpetrator in the acquaintance rape scenario. We discuss methodological difficulties in conducting this type of research and identify several directions for future research.